Security Guarantee for Vehicular Message Transmission Based on Dynamic Social Attributes. (20th December 2021) - Chen, Lishui; Wang, Jing; Chen, Xing; Zhang, Yifu
Abstract : Effective message forwarding between vehicles can reduce the occurrence of traffic accidents and improve the driving experience. Vehicle clustering can improve message utilization, but attackers in the network pose a serious threat to message forwarding. Based on vehicle clustering, we propose a message forwarding strategy for Vehicular Ad hoc Network. Specifically, the vehicles are clustered based on their directions and speeds. Besides, the friendship of vehicles is evaluated in terms of the interaction friendship and reference friendship. Based on the friendship of vehicles, the optimal vehicle can be selected as the cluster head. Thereafter, the double key technology is designed to encrypt vehicular messages such that the messages can be forwarded more safely and efficiently. The analysis results show that the proposed strategy can effectively improve the message delivery rate, reduce the message leakage rate, and improve the network performance.